Arthropoda (Acarina, Diptera) from subfossil layers in West Greenland. - Haarløv, Niels (Meddelelser om Grønland, 1967)
At Sermermiut, Jakobshavn, W.-Grl., arthropods (mites and diptera) were collected from a section covering a period of app. 2000 years, beginning in the middle of the second millenium B. C. With the technique employed only well sclerotinized, darkcoloured species were obtained. The animals found are probably contemporaneous with the layer in which they were collected. Zoogeographically the population contained species with a present arctic or arctic-northern distribution and was ecologically connected with bogs and humid heaths. The three most numerous Oribatei reproduced viviparously. The following species were new to Greenland: Epidamaeus spp., Jlfycobates consimilis, Eugamasus sp.